Pengembangan Strategi Perusahaan Percetakan Dengan Pendekatan Bisnis Model Canvas Dalam Menghadapi Era Digital - Rahman, Arif; Perdana, Surya; Widjajanto, Tulus (BULLET : Jurnal Multidisiplin Ilmu, 2024)
PT. XYZ is a printing company in Jakarta. The products produced by this company are newspapers, books, magazines, tabloids, brochures and also the Koran. In running its business, companies need the right strategy to be able to compete with competitors. The aim of this research is to develop a strategy for printing companies so they can survive in the digital era. The method used in this research is the Business Model Canvas approach. In this research, data was obtained from interviews with employees who work at the company PT. XYZ. The data obtained is then made into a business model on one canvas sheet which has nine key elements to analyze the company's business position. From the Business Model Canvas analysis, the printing business competition can be categorized as tight competition. Printing companies must improve the quality of their products and services to compete with other companies. Companies must also improve cost efficiency and enhance technological capabilities to increase their competitiveness. Companies must also improve their marketing capabilities to attract new customers and retain existing customers.